Do Plastic Surgery Residents Get Sued? An Analysis of Malpractice Lawsuits. Issue 1 (13th January 2023) - Gibstein, Alexander R.; Jabori, Sinan K.; Watane, Arjun; Slavin, Benjamin R.; Elabd, Rawan; Singh, Devinder
Abstract : Background: Trainees may be implicated in malpractice lawsuits. Our study examines malpractice cases involving plastic surgery trainees. Methods: Using the LexisNexis database, verdicts and settlements from appellate state and federal cases between February 1988 and 2020 were queried. A nonrepresentative sample of 300 cases was compiled. Results: During a 32-year period, 21 lawsuits involving plastic surgery trainees were identified. Of these, 14 (66.67%) involved claims when a trainee was directly named as a defendant. Eighteen (85.7%) cases were due to procedural-related adverse outcomes, while three (14.3%) cases were associated with clinical or diagnostic-related adverse outcomes. Of the procedure-related cases, five (27.8%) occurred when the trainee was the lead surgeon. Allegations included lack of informed consent of procedure complications (11, 52.4%), procedural error (11, 52.4%), failure to supervise trainee (11, 52.4%), inexperience of trainee (eight, 38.1%), incorrect diagnosis or treatment (five, 23.8%), delay in evaluation (three, 14.3%), lack of awareness of resident involvement (three, 14.3%), lack of follow-up (three, 14.3%), and prolonged operative time (one, 4.8%). Median time from injury to lawsuit resolution was 3.8 years [interquartile range (IQR), 3–5 years]. Verdicts were ruled in favor of the defense in eight (38.1%) cases and for plaintiff in six (28.6%) cases. A settlement was made in seven (33.3%) cases. Median payout for plaintiff-won cases was 5, 100, 000 (IQR, 1, 530, 000–17, 500, 000); the median settlement was 2, 500, 000 (IQR, 262, 500–4, 410, 000). Conclusions: Procedural error, improper informed consent, improper trainee supervision, and resident inexperience were the most common allegations. These factors can lead to financial and psychological burdens early in a physician's career.